Trans-Disciplinary Communication: Context and Semantics - Maurício Vieira Kritz (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Science is split into subject-oriented disciplines that are grounded on varying shades of the scientific method. Being a social activity, communication lays at the creative core of the sciencebuilding process of facts and explanations. To communicate means, in its most seminal sense, to bring something in common between distinct parts or to transfer something from one part to another. This 'commonality,' or what lays in common to the parts, can occur not just among persons but also among persons and nature or persons and non-human things. This article starts discussing communication at the human scale from the very beginning, widening the scope from its inner kernel in individuals towards social interactions in the scientific community. The perspectives, concepts, and guidelines unveiled by this exercise are applied in the article's text itself.